Implimentasi Tanggung Jawab Orang Tua Dalam Pendidikan Agama Islam di Keluarga Melalui Pendidikan Karakter(Studi di Desa Ngembat Kecamatan Gondang Kabupaten Mojokerto) - Nova Novitasari; Asmawi Asmawi; Khoirul Jazilah (Amaliyatu Tadris (AMYTA), 2023)
Responsibility is the ability to carry out the duties and obligations entrusted to a person to the best of one’s ability and to be willing to accept the consequences when those duties and obligations are not fulfilled. This study aims to analyze: (1) the implementation strategies of parental responsibility in Islamic Religious Education within the family through character education in Ngembat Village, Gondang District; and (2) the forms of implementation of parental responsibility in Islamic Religious Education within the family through character education in Ngembat Village, Gondang District. This research employs a qualitative approach, with data collection procedures carried out through observation, interviews, and documentation. Based on the research findings, it is known that the implementation strategies of parental responsibility in Islamic Religious Education within the family through character education in Ngembat Village, Gondang District include: (1) the exemplary strategy (role modeling), (2) the habituation strategy, and (3) the early childhood education strategy. Tanggung jawab adalah kesanggupan untuk menjalankan tugas dan kewajiban yang dipikul kepadanya dengan sebaik-baiknya dan sanggup menerima konsekuensi ketika tidak menjalankan tugas dan kewajibannya.Penelitian ini bertujuan untuk menganalisis: 1) Untuk mengetahui strategi pelaksanaan dari tanggung jawab orangtua dalam Pendidikan Agama Islam dikeluarga melalui pendidikan karakter di Desa Ngembat Kecamatan Gondang 2) Untuk mengetahui bentuk implementasi tanggung jawab orangtua dalam pendidikan Agama Islam dikeluarga melalui pendidikan karakter di Desa Ngembat Kecamatan Gondang. Metode penelitian yang digunakan kualitatif dengan prosedur pengumpulan data dengan cara observasi,wawancara dan dokumentasi. Berdasarkan hasil penelitian diketahui bahwa strategi pelaksanaan dari tanggung jawab orangtua dalam Pendidikan Agama Islam dikeluarga melalui pendidikan karakter di Desa Ngembat Kecamatan Gondang adalah 1) Strategi Keteladanan. 2) Strategi Pembiasaan. 3) Strategi Pendidikan Sejak Dini